Exploring the Effect of an eHealth Intervention on Women’s Physical Activity Behaviour: A Randomized Trial - Black, Melissa (Université d'Ottawa / University of Ottawa, 2020)
The rising number of women who are overweight or obese living in Canada is concerning because an excess weight can lead to serious health problems. Nearly 65% of women living in Canada are considered overweight or obese. Regular physical activity (PA) participation is beneficial and can help women manage their weight. Considering women who are overweight or obese are generally physically inactive, interventions drawing on theory are warranted to promote PA. This thesis reports on the protocol and results of a randomized controlled trial that was conducted to assess the effect of a self-determination theory-based eHealth intervention on PA among women who were overweight or obese with low levels of PA. The full protocol for this study is described in Chapter 3: Protocol Manuscript and the results of the primary objective are presented in Chapter 4: Results Manuscript. Reflections on the lessons I have learned while implementing a clinical trial are presented in Chapter 5: Lessons Learned. Briefly, the selfdetermination theory-based eHealth intervention provided (A) six weekly behavioural support emails, (B) a wearable activity tracker, and (C) a copy of the Canadian PA guidelines. The primary objective of this study was to determine if participants who received the combined intervention (A+B+C) increased their PA levels from baseline to post-intervention. The secondary objective was to assess if this combined intervention leads to greater change in PA than those who received an intervention including (B+C) or only (C). It was hypothesized that participants in the combined intervention would increase their PA from baseline to postintervention, and that this increase would be greater than the increase observed among those who received an intervention including (B+C) or only (C). In addition, measures of constructs embedded in self-determination theory (i.e., basic psychological need satisfaction and thwarting, motivational regulations) and wellbeing (i.e., affect, vitality, wellbeing) were included to address tertiary objectives of examining if there are differences in changes in these constructs between groups. Participants were recruited between September 2018 and March 2019. Data were collected using self-report and direct measures three times: at baseline (week 0), postintervention (week 7), and at follow-up (week 21). Data from forty-six women (Mage=37.72±11.87 years, MBMI=31.55±5.96 kg/m2 ) were analyzed. Mean PA at baseline across all participants was 1148.12±1091.03 metabolic equivalent minutes (MET-minutes) per week. In relation to the primary study objective, PA increased from baseline to post-intervention (F=17.95, p.05) and the interaction between group and time (p>.05) were not significant. In summary, participants in this study showed a large and significant increase in PA, but the three different interventions did not have a differential impact on change in PA. Discussion of the findings regarding the primary and secondary objectives, and the potential implications of the tertiary objective, will provide insight into which combination of intervention components may be more effective at promoting PA among insufficiently active women who are overweight or obese, and thus inform the design of future interventions aiming to promote PA.
Keywords: physical activity; intervention